Corporate Social Responsibility sebagai Implementasi Prinsip Tata Kelola Perusahaan Baik pada Asuransi Jiwa Bersama Bumiputra 1912 Cabang Padangsidimpuan - Linni Suraya Lubis (Economics, Business and Management Science Journal, 2023)
Corporate Social Responsibility (CSR) is a company's social responsibility towards its stakeholders. Good Corporate Governance (GCG) is a framework that regulates the relationships among various parties with interests in a company. One of the principles in Good Corporate Governance is the principle of responsibility, which generates the concept of Corporate Social Responsibility (CSR) as a manifestation of a company's responsibility to society and the environment. This research is a case study titled "Corporate Social Responsibility as an Implementation of Good Corporate Governance Principles in Bumiputera 1912 Life Insurance Branch of Padangsidimpuan." The aim is to assess whether Corporate Social Responsibility, as an implementation of Good Corporate Governance principles, can provide satisfaction to insurance customers. The research method uses descriptive analysis, collecting both primary and secondary data. Data is organized, interpreted, and analyzed to evaluate Corporate Social Responsibility as a form of implementing Good Corporate Governance principles. The research results demonstrate that Corporate Social Responsibility is one of the manifestations of the implementation of Good Corporate Governance principles and can provide satisfaction to insurance customers.